2016
DOI: 10.1016/j.mjafi.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The Alvarado score versus computed tomography in the diagnosis of acute appendicitis: A prospective study

Abstract: m e d i c a l j o u r n a l a r m e d f o r c e s i n d i a 7 2 ( 2 0 1 6 ) 3 3 2 -3 3Methods: A total of 320 patients with suspected acute appendicitis were included in this study over a period of 2 years. The Alvarado score was calculated for all of these patients and 112 CT scans were requested selectively by surgeons caring for the patients. The histopathology diagnosis was used as the gold standard against which diagnostic performance of Alvarado score and CT scan were compared.Results: The complete data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Details such as age, sex and ethnic origin of all the patients were recorded. Appendicitis inflammatory response score (AIR) [17,18], as well as the Alvarado score [20], were also calculated based on presenting symptoms and laboratory investigations simultaneously. The clinical risk of acute appendicitis was estimated and classified as necessary.…”
Section: Study Populationmentioning
confidence: 99%
“…Details such as age, sex and ethnic origin of all the patients were recorded. Appendicitis inflammatory response score (AIR) [17,18], as well as the Alvarado score [20], were also calculated based on presenting symptoms and laboratory investigations simultaneously. The clinical risk of acute appendicitis was estimated and classified as necessary.…”
Section: Study Populationmentioning
confidence: 99%
“…Many of the studies have documented utilization AS, and compared its scoring with CT and surgical outcomes. [23][24][25] Better clinical assessment and higher scores may help to avoid unnecessary CT examinations. 25 However, this may not be true in difficult cases and further imaging may be warranted to establish a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 At present, on the other hand, several reports have suggested a reduced clinical value in the use of advanced radiological methods. 11 Although its predictive power and use have been lowered recently, it is a widely known fact that the scores of 7 or greater are a strong predictor of AA. This study demonstrated that a high Alvarado score showed that abdominal pain may be secondary to AA with a sensitivity of 85% in patients with suspected AA and coexisting ovarian cysts.…”
Section: Discussionmentioning
confidence: 99%